Medical Cannabis Use and Pain: An Experience Sampling Study - Sznitman, Sharon Rodner; Rosenberg, Dennis; Vulfsons, Simon; Meiri, David; Greene, Talya (Frontiers in Psychiatry, 2021)
Background: Little research has tested associations of pain and MC use after long-term treatment and through methods that have external validity outside experimental settings. The study examined associations of pain, associated painful experiences, and long-term medical cannabis (MC) use in chronic pain (CP) patients using a naturalistic daily diary study that provided novel and externally valid data. Methods: Data were obtained from 78 MC users with CP three times daily over a 10-day period (nobservations = 1,688). Mixed-effects models were used to test the associations between MC use and momentary experiences of pain, affect, and fatigue. Results: Within persons, elevated experiences of pain intensity were associated with greater intention to use MC within the next hour. No evidence was found that the time lapse since last MC use was associated with pain levels, negative affect, or fatigue. Conclusions: The results imply that after long-term use, CP patients intend to use MC in response to pain experiences. Yet, they may not actually achieve the pain relief. More research is needed to examine whether continued MC use despite lack of pain relief is related to relief of other symptoms (e.g. dependence, withdrawal) or positive benefits (e.g. general sense of well-being) or tolerance.